Adoption of DSpace by Indian libraries. Issue 2 (4th April 2016) - Cherukodan, Surendran; S, Humayoon Kabir
Abstract : Purpose: – India occupies second position among the countries that have adopted DSpace open source software for institutional repositories (IRs)/digital libraries (DLs). The purpose of this paper is to examine the reasons for DSpace being preferred over other software. It inspects various instances of Indian web-based DSpace systems including the nature and growth of collection, the geographical distribution of DSpace systems and the types of institutions that adopt and maintain DSpace. Design/methodology/approach: – Data were collected from the official website of DSpace, Google search and from online discussion forums during July 2013 to January 2014. The 132 Indian DSpace links provided in the official DSpace website were examined. Further search was carried out on Google to identify Indian IRs and DLs that are not listed by the official website. A list of Indian DSpace websites prepared by the authors was sent to the online discussion forums for further updating. An online directory of Indian DSpace websites was created using WordPress which provided for the adding of comments. The study is limited to the web-based DSpace IRs and DLs in India. Findings: – The majority of the Indian IRs and DLs listed on the official website of DSpace are not visible on the internet. Many links lead to institution websites, commercial websites and personal pages of authors. Out of 132 DSpace links, only 55 are visible on the internet to search and use. Indian libraries prefer DSpace over EPrints, Fedora and Greenstone. Many institutions could not maintain continuity of their DSpace systems in the online environment. Institutions having more funding are maintaining web-based DSpace systems. The size, economic conditions, rate of literacy and number of universities in an Indian state do not influence the maintenance of digital systems. Academic institutions involving universities, technical institutions and colleges lead in the adoption and maintenance of web-based DSpace in India. Private universities and colleges have adopted DSpace for IR/DL. Public libraries constitute a minimum percentage of web-based DSpace instances. Indian courts and Parliament have adopted DSpace. Shodhganga, the Indian ETD project, is running on DSpace. Originality/value: – This is the first paper examining the adoption of DSpace by Indian libraries with a focus on online visibility and the strength of collection. It can be used to understand the pattern of technology adoption by Indian libraries over the years.